Survey of IoT security research: threats, detection and defense - Yiyu YANG; Wei ZHOU; Shangru ZHAO; Cong LIU; Yuhui ZHANG; He WANG; Wenjie WANG; Yuqing ZHANG (Tongxin xuebao)
Based on the IoT security literatures published in the international conferences on network security (ACM CCS, USENIX Security, NDSS, IEEE S＆amp;P) in recent five years, and other prominent researches, the works from the perspective of ＆quot;threat, detection, defense＆quot; were systematically summarized and analyzed.Firstly the basic architecture of the IoT system was introduced.Then the main threats proposed in these works were classified into eight categories, and the causes and hazards of the threats were analyzed.After that, six detection and five defense schemes against these threats were introduced, and their technical principles, advantages and disadvantages were compared.At last, on the basis of the above analysis, the main challenges that the current research still faces were put forward, and the research directions of future works were point out.